URGENSI PENDAMPINGAN PENDAFTARAAN HAK CIPTA BAGI PENCIPTA LAGU SEBAGAI UPAYA MELINDUNGI IDENTITAS KARYA DAN KEASLIAN KREASI SENI - Sartono, Latifah Nurjannah; Abdillah, Alisya Afifah Maulidina Putri; Saroy, Geraldo Virasakti Abiyyudha; Kusuma, Dimas Andrianto; Farhan, Alif; Yulianti, Melisa; S., Nikolas Andika; Yuniar, Divia Avril; Putri, Belinda Ayu Sabina; Rahmawati, Aulia Vani; Baety, Anti Navirotul; Putro, Herjuno; Rahmawati, Alicya; Hasibuan, L.Ma Naf’iyyah; Hakim, Muhammad Defa; Attalah, Oemar; Putri, Prasida Alya; Aulia, Dea Risti; Tarigan, Veronica Nora Litna (Zhata Institut, 2025)
Musical artworks are creations that have high aesthetic musicians and intellectual value and play an essential role in the development of culture and the creative economy. However, the lack of understanding of the importance of legal protection of such works, particularly through copyright registration, is a significant obstacle for many indie musicians. This condition makes their works vulnerable to misuse, plagiarism, or unauthorized exploitation, ultimately harming the creator morally and materially morally and materially. This article discusses the implementation of counseling activities and copyright registration assistance for indie musicians in Semarang City as part of efforts to protect musical artworks in facing the challenges of the digital era. This article discusses the activities of counseling and assistance in copyright registration for indie musicians as a step to protect their musical artworks. Using a participatory approach, this program aims to increase musicians' understanding of the benefits and procedures of copyright registration so that their works can be protected from misuse or infringement of rights. The results of the activity show that direct socialization and intensive mentoring are effective in increasing indie musicians' awareness and understanding of copyright. This effort is expected to strengthen the local music community and support the growth of Indonesia's stable and sustainable music industry